MENAKAR EKSISTENSI LEMBAGA PENDIDIKAN PESANTREN DI TENGAH PANDEMI COVID-19 - Damayanti, Eka; Budi, Rosdinaman; Susilawati, Sumarni; Syafruddin, Baso (Universitas Islam Negeri Alauddin Makassar, 2021)
Islamic boarding schools are one of the educational institutions in Indonesia that have been affected since the Covid 19 pandemic. Islamic boarding schools continue to exist with various creative management practices. This article aims to describe the efforts that Islamic boarding schools have made to exist during the Covid-19 pandemic. This research is a library research study using journals and reference books as a focus of the research study. Data were analyzed using content analysis. The results showed that Islamic boarding schools have been facing various challenges since their inception, during colonialism, and during modernization, and now, during the Covid-19 pandemic. As an Islamic educational institution whose presence is very important in society, the Islamic boarding schools have made adjustments to the conditions that occur, including adjustments in the form of economic independence and adjustments in learning using information technology. This was done so that Islamic civilization would not decline, even became an option of other modern schools to create a generation with character, insight, and good morals.